Biologic drugs in chronic spontaneous urticaria - Licari, Amelia; Manti, Sara; Leonardi, Salvatore; Minasi, Domenico; Caffarelli, Carlo; Cardinale, Fabio; Miraglia Del Giudice, Michele; Calvani, Mauro; Ciprandi, Giorgio; Marseglia, Gian Luigi (Acta Biomedica Atenei Parmensis, 2021)
Chronic spontaneous urticaria (CSU) is a condition defined by the presence of recurrent urticaria, angioedema, or both, which persist for more than six weeks in duration and occurs in the absence of an identifiable trigger. Both children and adults can develop CSU, although it is more common in adults and in women than in men, with a peak occurrence in the third to fifth decades of life. It imposes a significant burden on patients, families and healthcare systems. The goal of therapy in patients with CSU is to achieve a level of symptom control and improvement in quality of life that is acceptable to the patient, while minimizing therapy-related side effects. The recent introduction of biologic drugs has changed the management of the disease. This work aims to provide a narrative review of the current state of biological therapy and the promising drugs under development for CSU.